Analysis The Flood Resulting From Supposed Collapse About AL-THAWRA Dam And Put The Flood Maps - الدرويش حسين; منذر حماد (Latakia University Journal -Engineering Sciences Series, 2023)
This research involves analysis The Flood Resulting from Supposed Collapse About AL THAWRA Dam in Alsanober basin in Lattakia governorate. Where the mathematical model of the study area was built using the topographic maps at various scales with the digital elevation model, collecting data related to dam and reservoir, predict the parameters of the expected breach by applying equations (XU, Y. and Zhang, 2009) namely: The height of the breach formed, the width of the breach, the lateral inclinations, time required to develop the breach. by using the software: Arc GIS, Google Earth, HEC-RAS, We have come up with inundation maps that show the areas affected by the maximum water speeds and the great water depths, according to the cause of the collapse, to be used in the development of emergency plans. The results of the worst scenario were the collapse resulting from the overtopping, a flood wave of great abundance 5503 m3/sec, the result is an hour after the start of the collapse, Where the breach reaches its final form after an hour and 34 minutes. The average velocity of a flood wave ranges from (2.39 - 26) m/sec along the stream and the water depths ranged from 6 to 19 meter, it is shown on the immersion maps. human losses may occur unless a warning and evacuation is given in time.